3D Visualization of Furniture in A Room with Augmented Reality - Adi Kusuma, Hatha Jaya; Zakariyah, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to make it easier for people who want to organize furniture better and more effectively. No need to spend money or effort; just by scanning the camera in the room, furniture objects will appear. With augmented reality technology, this problem can be solved by implementing an application that can visualize 3D objects in the real world simultaneously. The method used in the research is the MDLC (Multimedia Development Life Cycle) method. The previous problem was the arrangement of furniture, which still uses manual methods. Shifting real objects from corner to corner will take a long time. The result is that the application is feasible to be used by the community to organize the room virtually by shifting objects through a more effective cellphone screen. The success test rate in this application is 88.75%.